2019
DOI: 10.1016/j.scitotenv.2018.12.169
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of multiple global virtual material flows

Abstract: This study presents the first comprehensive assessment of evolution of six kinds of global networks.• The volumes of all water, energy, CO 2 , nitrogen and financial capital flows increased over time while land flow decreased.• The top five trade countries accounted for a surprisingly large proportion (47% to 80%) of total trade volumes. • Different kinds of virtual material flows tended to enhance each other through synergistic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
0
17
1
1
Order By: Relevance
“…It is also worth noting how environmental layers are mostly uncorrelated. Even CO 2 shows no significant correlation with energy, a result that contradicts previous studies on the global multiple virtual material flows network [15]. On a global scale CO 2 and energy show the strongest nexus, foremost for flows in the opposite direction, with an increasing trend beginning with the 2000s.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…It is also worth noting how environmental layers are mostly uncorrelated. Even CO 2 shows no significant correlation with energy, a result that contradicts previous studies on the global multiple virtual material flows network [15]. On a global scale CO 2 and energy show the strongest nexus, foremost for flows in the opposite direction, with an increasing trend beginning with the 2000s.…”
Section: Discussioncontrasting
confidence: 86%
“…The transfer of embodied emissions flows in commodity production affects the environmental system in trading area [32,33]. Xu et al [15] (2018) found that, over time, all flows between distant countries are increased more than those between adjacent countries. Furthermore, large increases in virtual resource flows also affect the financial capital flows between countries [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, countries may be metacoupled (e.g., through trade between adjacent countries and between distant countries) 47 , and a shorter distance between sending and receiving countries plays a crucial role in increasing meat trade 6 . Distance has also been shown to be very important in the trade of other products 48,49 , as well as in other human activities such as global fishing 50 , tourism [51][52][53] , and flows of ecosystem services [54][55][56] . Third, income level and population size have been found to be important determinants of global meat trade 1,2 .…”
Section: Methodsmentioning
confidence: 99%
“…As the economic links between regions continue to intensify through trades of various goods, the transboundary dependencies of production and consumption have become an increasingly important driver of environmental impacts, including land resource uses [8]. Linking the land resource use to the whole production chain and final consumption of various products and services offers a new perspective to understand and manage the environmental impact of anthropogenic activities [9,10,11]. Similar to water, energy, air pollution, and other issues [12,13,14,15], the accounting of land resources embedded into commodities in trades helps identify the displacement of land uses and appropriate responses of the resource consumption based on final consumption of inhabitants, and is; thus, useful in informing policymakers on the magnitude of external environmental burdens imposed by certain regions [16].…”
Section: Introductionmentioning
confidence: 99%